(untitled) (Nepal Medical College Journal, 2020)
The ideal management of cholecysto-choledocholithiasis is an open cholecystectomy (OC) with the common bile duct (CBD) exploration worldwide. The single setting 2-stage approach- endoscopic retrograde cholangiopancreatography (ERCP), endoscopic sphincterotomy (EST), and CBD clearance followed by laparoscopic cholecystectomy (LC) offers an advantage, mainly by reducing the hospital stay, the cost, and the morbidity. The Objective of the study is to compare the ERCP+LC single setting approach with an OC+CBD exploration for the treatment of cholecysto-choledocholithiasis. This is an interim analysis of 160 patients with 83 (51.9%) patients in ERCP+LC and 77 (48.1%) in an open procedure (OC+CBD exploration) group respectively. We did a prospective study in patients admitted for the management of the cholecysto-choledocholithiasis in the Department of Surgery at the Lumbini Medical College and Teaching Hospital from November 2012–October 2015. They underwent 2-stage ERCP+LC in a single setting and we compared them with 2-stage OC+CBD exploration in a single setting approach. The patients with the open procedure were our control group. All the included cases in the study were elective. The procedure was feasible in our hospital. Similarly, the hospital stay was significantly shorter in the ERCP+LC group; 3.92±0.719 days vs 10.30±1.557 days, p <0.05. There was a significant difference in the total morbidity of ERCP+LC group 7 (8.4%) vs 14 (18.2%), p <0.05. Here, wound infection in the ERCP+LC group was 2 (2.4%) vs 4 (5.2%) and there was one case of abdominal collection 1 (1.2%) which was managed symptomatically. The incidence of retained CBD stone in the ERCP+LC was 3 (1.2%) which was managed successfully with ERCP. In all the cases, post- ERCP amylase value was found to be within the normal limit. The result of our study suggests, single setting ERCP+LC at the peripheral-level hospital is feasible in terms of cost, length of hospital stay, morbidity and stone clearance.